Butylidenephthalide Blocks Potassium Channels and Enhances Basal Tension in Isolated Guinea-Pig Trachea. (9th July 2014) - Hsu, Hsin-Te; Yang, You-Lan; Chen, Wan-Chen; Chen, Chi-Ming; Ko, Wun-Chang
Abstract : Butylidenephthalide (Bdph, 30 300 μ M), a constituent of Ligusticum chuanxiong Hort., significantly enhanced tension in isolated guinea-pig trachea. In this study, we investigate the mechanism(s) of Bdph-induced contraction in the tissue. Isolated trachea was bathed in 5 mL of Krebs solution containing indomethacin (3 μ M), and its tension changes were isometrically recorded. Cromakalim (3 μ M), an ATP-dependent K + channel opener, significantly antagonized the Bdph-induced enhancement of baseline tension. Bdph (300 μ M) also significantly antagonized cromakalim-induced relaxation. Bdph (300 μ M) did not significantly influence the antagonistic effects of glibenclamide (GBC, 1 μ M) and tetraethylammonium (TEA, 8 mM) against the cromakalim-induced relaxation. However, Bdph (300 μ M) and 4-aminopiridine (4-AP, 5 mM), a blocker of K v 1 family of K + channels, in combination significantly rightward shifted the log concentration-relaxation curve of cromakalim. The antagonistic effect of the combination almost equals the sum of the individual effects of Bdph and 4-AP, suggesting that the antagonistic mechanism of Bdph may be similar to that of 4-AP. All calcium channel blockers influenced neither the baseline tension nor antagonistic effect of Bdph against cromakalim. In conclusion, Bdph may be similar to 4-AP, a blocker of K v 1 family of K + channels, to enhance the baseline tension of guinea-pig trachea.